Development of a reduced-scale electric vehicle for testing driving aid systems - Marques, Gonçalo Pereira (2020)
The main objective of this dissertation is the design and physical conception of a reduced-scale vehicle, characterised by being electric and with an in-wheel motor configuration, allowing All-Wheel Drive (AWD) traction configuration and independent control of each wheel. The purpose of this vehicle construction is to serve as a test platform for driving aid systems, therefore being endowed with sensorial electronics. A requirement set is that the developed prototype includes a suspension system, so that its dynamic behaviour resembles as much of reality as possible. The entire process of design and construction of the model is shown in detail in the course of the document, serving as a guide that intends to justify all decisions and steps taken. At the end of this project, several test routines were carried out, allowing to classify the use of this model for future implementation of driving aid systems as viable, and making it possible to set all the initially stipulated objectives as complete.